Students' Concept Understanding Ability Through Inquiry Approach to Series and Series Materials - Verawati Rouli BN; Tika Dwi Nopriyanti; Dina Octaria (Journal on Education, 2023)
Research This study aims to determine students' conceptual understanding abilities through an inquiry approach. The type of research used is quantitative with a one case shoot study treatment design. The subjects in this study were 30 students of class XI IPA 2 at SMA Negeri 14 Palembang. The data collection technique in this study is test data. Data analysis techniques using quantitative descriptive statistics. Based on the research data, it can be concluded that students' conceptual comprehension abilities through an inquiry approach to sequences and series material in class XI IPA 2 SMA Negeri 14 Palembang have a good average. This can be seen from the results of the study, namely the average final test score for students' conceptual understanding ability was 75.50.